SEGMENTASI KONSUMEN OCEAN EDUCATION BERBASIS INTENSI DAN MOTIVASI SISWA SEBAGAI DASAR PENGEMBANGAN STRATEGI KOMUNIKASI PEMASARAN - Malindo Putra, Syahrizan
Educational transformation is carried out by the Indonesian government to improve the quality of national education quality by making changes to the university entrance selection system. Major changes occurred in Seleksi Nasional Berbasis Tes (SNBT) which only focuses on reasoning ability and language literacy. The changes in SNBT selection open up new opportunities for Ocean tutoring in increasing the number of consumers, especially in the SNBT class program. Market segmentation that has not been carried out is the main problem for Bimbel Ocean to determine the main target market for the SNBT class program. As a result, the marketing communication strategy of Bimbel Ocean has not been effective so that there are not many consumers know about the SNBT class program at Bimbel Ocean. This study aims to identify the main variables that influence students' intention and motivation to attend tutoring. Therefore, a model was built based on previous research relevant to intention and motivation. The model was analyzed using the partial least squares structural equation modeling (PLS-SEM) technique to identify the main variables that influence students' intention and motivation to attend tutoring agency. However, to make it easier for Bimbel Ocean to determine the target market, latent class clustering analysis with a finite mixture partial least squares technique was conducted to form consumer segments based on the main variables. The result of this study is that there are two segments formed based on differences in the main variables that influence students' intentions and motivations in joining tutoring agency, namely "Ambitious Students" and "Volatile Students". The selected target segment is the first segment, namely "Ambitious Students", a segment whose intention and motivation to take tutoring is influenced by a great desire from students to improve academic performance at school by attending tutoring in their leisure time. The findings of this research are used to design recommendations for marketing communication strategies.